2013
DOI: 10.1111/jace.12356
|View full text |Cite
|
Sign up to set email alerts
|

Complex Impedance Spectra of Polymer‐Derived Silicon Oxycarbides

Abstract: The complex impedance spectra of polymer-derived amorphous silicon oxycarbides synthesized at different temperatures are reported. Analysis of the spectra using equivalent circuit models showed that the conduction of current is dominantly through the matrix and free carbon in series, instead of through the matrix or free carbon only. We found that the conductivity of both matrix and free-carbon phase increases with increasing synthesis temperature, whereas the relaxation time of the matrix is much shorter than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…The disks were finally pyrolyzed at different temperatures of 1000°C, 1100°C, 1200°C, and 1300°C for 4 h under the protection of flowing ultrahigh purity argon. The obtained materials were amorphous with the composition of ~SiC 1.45 O 0.08 , independent of pyrolysis temperature; the small amount of oxygen is likely due to the contamination during material synthesis …”
Section: Methodsmentioning
confidence: 96%
“…The disks were finally pyrolyzed at different temperatures of 1000°C, 1100°C, 1200°C, and 1300°C for 4 h under the protection of flowing ultrahigh purity argon. The obtained materials were amorphous with the composition of ~SiC 1.45 O 0.08 , independent of pyrolysis temperature; the small amount of oxygen is likely due to the contamination during material synthesis …”
Section: Methodsmentioning
confidence: 96%
“…Haluschka et al [18] reported a strong frequency-dependent conductivity in polymerderived silicon carbonitride, and attributed the phenomenon to a large polaron tunneling process [18]. Wang and co-workers [24] reported the complex impedance spectra of the polymer-derived silicon oxycarbide ceramics. However, AC conductive behavior has never been investigated in detail for polymer-derived ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Such a unique nanostructure conveys to these materials an exceptional mix of properties combining high elastic modulus and excellent chemical durability, [5][6][7] with optical, 8 electrochemical, 9 and electrical properties 10 which make SiOCs good candidate materials for LED, 11 anodes for Li-ion batteries 12,13 and pressure and temperature sensors for harsh environments, 14 respectively. The amount and structure of the free carbon phase of silicon oxycarbides have been shown to influence many different properties such as the stability of the amorphous network and its crystallization kinetics, 15 the electrical 16,17 and optical properties, 18 as well as the Li storage capacity when SiOCs are used as anodes for Li-ion batteries. 19 Accordingly, the free carbon phase present in the SiOC nanostructure has been extensively characterized using different techniques 1 and also modeled by ab initio molecular dynamic simulation.…”
Section: Introductionmentioning
confidence: 99%